CURRENT STATE AND DEVELOPMENT PROSPECTS OF INFRASTRUCTURE IN CITIES AND SETTLEMENTS OF THE NAVOI REGION - Nayimov Shokhidjon Orifboyevich (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Abstract: This article analyzes the state policy, legal and regulatory framework for the development of urban infrastructure in the Republic of Uzbekistan, as well as their significance in regional development. Issues regarding the modernization of urban infrastructure, the effective management of urbanization processes, the improvement of engineering and communication networks, and the provision of quality services to the population are highlighted. During the study, urban infrastructure development trends were studied based on the reforms being implemented in the country, state programs, and regulatory legal acts. According to the research results, the comprehensive urban policy implemented by the state serves to increase the economic potential of cities, strengthen their investment attractiveness, and improve the quality of life for the population.